CLOUD TECHNOLOGIES AS A FACTOR IN INCREASING COMPANY EFFICIENCY - SEMENENKO, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the impact of cloud technologies on increasing the efficiency of companies in the modern context of globalization and digital business transformation. Cloud solutions have become an important element of the innovative infrastructure of enterprises, allowing them to optimize business processes, reduce costs, and enhance operational flexibility. The use of cloud technologies, such as SaaS, PaaS, and IaaS models, enables companies to effectively manage resources and reduce the need for capital investments in IT infrastructure. The main focus is on the economic impact of cloud technologies, including their ability to lower capital expenditures, which gives businesses the opportunity to more flexibly manage financial resources and respond quickly to changing market conditions. Special attention is given to improving productivity through business process automation and internal collaboration via cloud platforms. The article analyzes specific examples of cloud solutions used by both large and small enterprises to increase operational efficiency and competitiveness. The article also analyzes the role of cloud technologies in crisis situations, such as economic downturns or global challenges. Cloud solutions help companies adapt to change, ensuring high flexibility, accessibility of technologies, and efficient resource management during periods of instability. Practical case studies are considered, where the transition to cloud technologies not only allowed companies to maintain business continuity but also improved their market positions. Based on the analysis, it is concluded that cloud technologies are a key factor in enhancing the efficiency of companies in the modern economy. They not only help reduce costs but also create new opportunities for business development, innovation, and competitiveness on a global scale. Recommendations are provided for the effective implementation of cloud solutions in companies of different sizes and industries, as well as perspectives for further research in this field.